A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil - Marciano-Jr, Euvaldo; Lantyer-Silva, Amanda Santiago F.; Solé, Mirco (Zootaxa, 2017)
We describe a new species of Phyllodytes from Ilhéus (15º04’S, 39º03’W; 95 m above sea level), south of state of Bahia, in the northeastern Atlantic Forest of Brazil. Phyllodytes megatympanum sp. nov. is diagnosable by the following combination of characters: (1) dorsum of body, arms, and legs uniformly light brown; (2) groin yellow; (3) snout pointed in dorsal view, protruding in profile; (4) tympanum large with a round distinct tympanic annulus; (5) adult males with two anterior large odontoids followed by a series of smaller odontoids on each side of the mandible; (6) well-developed tubercle near tibio-tarsal joint; (7) advertisement call composed of a series of 12 to 19 unpulsed notes, with harmonic structure and (8) mean dominant frequency of 3.98 kHz.